Analisis Konsep Independensi Dewan Pengawas Syariah dalam Penerapan Prinsip Syariah di Lingkungan Perbankan Syariah - Zulbaidah Zulbaidah; Mia Lasmi Wardiyah; Bobang Noorisnan Pelita; Dedi Supriyadi; Nurul Hasana (Fakultas Ekonomi Universitas 45 Surabaya, 2023)
The Sharia Supervisory Board is obliged to direct, review, and supervise the activities of financial institutions so that it can be believed that they comply with Islamic sharia rules and principles, the fatwa of the Sharia Supervisory Board rules binding the Islamic financial institutions. The Shari'ah Supervisory Board has a heavy and strategic task so it takes a high professional to live it.The objectives of this research are: To find out the role of the Sharia Supervisory Board in supervising and handling the issue of Compliance with Islamic principles in Islamic Banking; To find out the obstacles faced by the Sharia Supervisory Board in upholding sharia economic principles in Sharia Banking; and to find out the steps shown by the Sharia Supervisory Board in upholding the principle of Independence in Sharia Banking.This research uses a conceptual approach that explains the concept of the independence of the Sharia Supervisory Board in carrying out sharia supervision activities in sharia banking.The result of this research is that Supervision in Sharia Banking is carried out to ensure the suitability of all bank operations with sharia principles and rules, namely by issuing fatwas, rules, and directives in fiqh issues which are used as guidelines for management in operating Islamic banks. With regard to independence, members of the Sharia Supervisory Board must not be part of the employees of the Islamic bank. Although he was appointed by the General Meeting of Shareholders, however, the matter of approval must come from the National Sharia Board. The Shari'ah Supervisory Board also has a work system and certain tasks as do other oversight bodies. The absence of influence from directors, commissioners and employees in Sharia Banking is able to shake the decision of the Sharia Supervisory Board in assessing fund distribution and internal audit activities in the Sharia compliance report in Sharia Banking.